2019
DOI: 10.3847/2041-8213/ab04b1
|View full text |Cite
|
Sign up to set email alerts
|

The Simultaneous Formation of Cored, Tangentially Biased, and Kinematically Decoupled Centers in Massive Early-type Galaxies

Abstract: We study the impact of merging supermassive black holes (SMBHs) on the central regions of massive early-type galaxies (ETGs) using a series of merger simulations with varying mass ratios. The ETG models include realistic stellar and dark matter components and are evolved with the gadget-3 based regularized tree code ketju. We show that observed key properties of the nuclear stellar populations of massive ETGs, namely flat stellar density distributions (cores), tangentially biased velocity distributions and kin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 53 publications
7
58
1
Order By: Relevance
“…In general, massive early-type galaxies, like these two galaxies, show negative orbital anisotropy parameters in their central regions, indicating tangential orbits; on the contrary, in the outer regions, the orbits appear radial (Thomas et al 2014;Rantala et al 2019). Numerical simulations show that this difference in the stellar orbits might originate if massive elliptical galaxies form from the merging of two progenitors with mass ratios larger than 1{3 (Rantala et al 2019): at the centre of the newborn galaxy, the gravitational torques caused by the merging of the SMBHs of the two parent galaxies cause a reversal of the orbit behaviour, from radial to tangential. Therefore, because we assume below an orbital anisotropy parameter β independent of radius r, we exclude the innermost 2 arcsec in the kinematic profiles of NGC 4486 and NGC 5846.…”
Section: Ngc 4486 and Ngc 5846mentioning
confidence: 89%
“…In general, massive early-type galaxies, like these two galaxies, show negative orbital anisotropy parameters in their central regions, indicating tangential orbits; on the contrary, in the outer regions, the orbits appear radial (Thomas et al 2014;Rantala et al 2019). Numerical simulations show that this difference in the stellar orbits might originate if massive elliptical galaxies form from the merging of two progenitors with mass ratios larger than 1{3 (Rantala et al 2019): at the centre of the newborn galaxy, the gravitational torques caused by the merging of the SMBHs of the two parent galaxies cause a reversal of the orbit behaviour, from radial to tangential. Therefore, because we assume below an orbital anisotropy parameter β independent of radius r, we exclude the innermost 2 arcsec in the kinematic profiles of NGC 4486 and NGC 5846.…”
Section: Ngc 4486 and Ngc 5846mentioning
confidence: 89%
“…Tsatsi et al (2015) showed that kpc-sized KDCs can also form in a prograde merger of two disk galaxies during which reactive forces create short-lived reversal of the orbital spin. Rantala et al (2019) shows that KDCs may also arise from orbit reversals of the central SMBH caused by gravitational torques from expelled material in the dissipationless merger of two massive ETGs. For binary mergers of massive ETGs (each M * > 8 × 10 10 M ) with very massive SMBHs (each > 10 9 M ), they even find multiple KDCs, similar to what we found in FCC 47, however, the simulated KDCs still share a single rotation axis aligned with the minor axis of the galaxy.…”
Section: Evidence For Merger History Of Fcc 47mentioning
confidence: 99%
“…Large IFS surveys such as SAURON (Bacon et al 2001) or ATLAS3D have revealed that a significant fraction of ETGs have a KDC, especially slow-rotators ). Simulations suggest that the formation of KDCs is triggered by major mergers (Jesseit et al 2007;Bois et al 2011;Tsatsi et al 2015), but once formed, a KDC can be stable over a long time in a triaxial galaxy (van den Bosch et al 2008;Rantala et al 2019). KDCs are not rare in slow-rotating galaxies like FCC 47, however two decoupled components certainly are.…”
Section: Galaxy Lightmentioning
confidence: 99%
“…A more readily observable kinematic consequence is a possibility of KDC formation from the interaction between the SMBHs and the surrounding stellar body. As SMBHs pass and exert torques on each other, there is a switch of the angular momentum between the SMBHs (and stars under their direct gravitational influence) and the rest of the galaxy, possibly producing nested KDCs (Rantala et al 2019). Because the core formation is enhanced if the SMBHs are massive, and because such SMBHs live in massive galaxies (e.g.…”
Section: Formation Of Stellar Coresmentioning
confidence: 99%